Expression of cilium-associated genes defines novel molecular subtypes of idiopathic pulmonary fibrosis. Issue 12 (19th June 2013) - Yang, Ivana V; Coldren, Christopher D; Leach, Sonia M; Seibold, Max A; Murphy, Elissa; Lin, Jia; Rosen, Rachel; Neidermyer, Amanda J; McKean, David F; Groshong, Steve D; Cool, Carlyne; Cosgrove, Gregory P; et al.
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is an untreatable lung disease with a median survival of only 3–5 years that is diagnosed using a combination of clinical, radiographic and pathologic criteria. Histologically, IPF is characterised by usual interstitial pneumonia (UIP), a fibrosing interstitial pneumonia with a pattern of heterogeneous, subpleural regions of fibrotic and remodelled lung. We hypothesised that gene expression profiles of lung tissue may identify molecular subtypes of disease that could classify subtypes of IPF/UIP that have clinical implications. Methods and findings: We collected transcriptional profiles on lung tissue from 119 patients with IPF/UIP and 50 non-diseased controls. Differential expression of individual transcripts was identified using an analysis of covariance (ANCOVA) model incorporating the clinical diagnosis of each patient as well as age, gender and smoking status. Validation was performed in an independent cohort of 111 IPF/UIP and 39 non-diseased controls. Our analysis identified two subtypes of IPF/UIP based on a strong molecular signature associated with expression of genes previously associated with fibrosis (matrix metalloproteinases, osteopontin, keratins), cilium genes and genes with unknown function. We demonstrate that elevated expression of cilium genes is associated with more extensive microscopic honeycombing and higher expression of both the airway mucin gene MUC5B and the metalloproteinase MMP7, a gene recently implicated in attenuating ciliated cell differentiation during wound repair. Conclusions: Expression of cilium genes appears to identify two unique molecular phenotypes of IPF/UIP. The different molecular profiles may be relevant to therapeutic responsiveness in patients with IPF/UIP.